The Political Influence of Translation in a time of Revolution and War in France: a Microhistory of two Irish translators Nicholas Madgett (1738-1813) and John Sullivan (1767-1802) - Gleeson, John (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of French, 2024)
This thesis is an interdisciplinary study of two Irish translators, Nicholas Madgett and John Sullivan, incorporating approaches from translation studies and history. Drawing principally on French archival sources, the thesis begins with a microhistorical profile of the two translators that connects to the broader political landscape of the French Revolution. A detailed analysis of their translation practice is embedded in the historical context of the period. Translation may be causative, and not merely refractive of historical events. The confluent functions assumed by the translators such as propaganda and political advocacy complement and enhance the influence of their translations. The focus on the political influence of translation is an important contribution to the historiography of translation, as the historical role of translation is often neglected or misunderstood by historians. Madgett and Sullivan were recruited by the new Republican government in France in 1793. The microhistory of the two translators, and the review of their translations provide a structured, interdisciplinary response to the principal research question: whether Madgett and Sullivan's translations, and their confluent, bilingual functions exerted a political influence on historical events in France in a time of Revolution and war?
APPROVED
Keywords: Translation History; French Revolution; Nicholas Madgett and John Sullivan; Political Influence of Translation